1994
DOI: 10.1055/s-2006-959522
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Radical Scavenging Effects of Aged Garlic Extract and its Constituents

Abstract: The antioxidant properties of three garlic preparations and organosulfur compounds in garlic have been determined. Aged garlic extract inhibited the emission of low level chemiluminescence and the early formation of thiobarbituric acid-reactive substances (TBA-RS) in liver microsomal fraction initiated by t-butyl hydroperoxide. However, the water extracts of raw and heat-treated garlic enhanced the emission of low level chemiluminescence. Among the variety of organosulfur compounds, S-allylcysteine (SAC) and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
216
3
17

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(251 citation statements)
references
References 0 publications
6
216
3
17
Order By: Relevance
“…Non-enzymatic antioxidant activity of garlic extract was also reported by Yin et al (2002). However, according to some authors (Amagase et al, 2001;Imai et al, 1994), this antioxidant activity (AOX) was more attributed to the organosulfur compounds. Statistical analysis also showed that radical scavenging activity, reducing capacity, scavenging of hydrogen peroxide and chain-breaking activity (initial and after heating) were highly correlated with total phenolics content of extracts, and coefficients of determination (r 2 ) ranged from 0.90 and 0.95.…”
Section: Total Phenolicsmentioning
confidence: 70%
“…Non-enzymatic antioxidant activity of garlic extract was also reported by Yin et al (2002). However, according to some authors (Amagase et al, 2001;Imai et al, 1994), this antioxidant activity (AOX) was more attributed to the organosulfur compounds. Statistical analysis also showed that radical scavenging activity, reducing capacity, scavenging of hydrogen peroxide and chain-breaking activity (initial and after heating) were highly correlated with total phenolics content of extracts, and coefficients of determination (r 2 ) ranged from 0.90 and 0.95.…”
Section: Total Phenolicsmentioning
confidence: 70%
“…In addition to these benefits, some garlic preparations have been reported to possess hepatoprotective, immune-enhancing, anticancer and chemopreventive activities. Some preparations appear to be antioxidative, whereas others may stimulate oxidation (Imai et al, 1994). The cardiovascular-protective effects of garlic have also been evaluated extensively in recent years (Yeh and Liu, 2001).…”
mentioning
confidence: 99%
“…Katsuki et al (2006) reported an inhibitory effect of SAC observed in a DMH-induced colorectal carcinogenesis experiment using mice. Garlic smell derived from sulfide components was reduced by autoclave treatment in HTPG, and the color of the powder became brown due to the Maillard reaction, suggesting that HTPG is similar to aged garlic extract (prepared by long-term aging of sliced raw garlic in alcoholic water (Amagase, 2006)) and fermented garlic (or black garlic) (Sato et al, 2006a;Sasaki et al, 2007;Wang et al, 2010), and contains S-allylmercaptocysteine, fructosyl arginine, and tetrahydro-β-carboline derivative, in addition to SAC (Imai et al, 1994;Ryu et al, 2001;Ichikawa et al, 2006;Sato et al, 2006b). A Korean research group which initially reported the HTPG production method identified an antioxidative substance, thiacremonone (Hwang et al, 2007), and showed that this substance alone exhibited an anticancer effect on human colon cancer cells and strengthened the growth inhibition effect of chemotherapeutic drugs (Ban et al, 2007;Ban et al, 2009).…”
Section: Discussionmentioning
confidence: 99%